Symbolika „zwierzęca” w twórczości Güntera Grassa - Głuszko-Boczoń, Estera (Motywy fauny i flory w literaturze i kulturze, 2018)
The article aims to present diversity of animal symbolism in the work of the German Noble laureate. The animal motif — from dog to snail — is frequently explored by Grass. In numerous works, the animal plays a prominent role which allows to read the content in a multidimensional way. The animals foreshadow the future, forewarn and encourage reflection. They become a motif that gives room to further contemplation.